Comparative Analysis of Genomics and Proteomics in the New Isolated Bacillus thuringiensis X022 Revealed the Metabolic Regulation Mechanism of Carbon Flux Following Cu2+ Treatment - Quan, Meifang; Xie, Junyan; Liu, Xuemei; Li, Yang; Rang, Jie; Zhang, Tong; Zhou, Fengjuan; Xia, Liqiu; Hu, Shengbiao; Sun, Yunjun; Ding, Xuezhi (Frontiers in Microbiology, 2016)
Bacillus thuringiensis (Bt) X022, which showed strong insecticidal activity against several Lepidopteran pests, is a novel strain isolated from soil in China. In this work, we performed whole genome sequencing of this Bt strain using the next-generation sequencing technology, and further conducted a comparative analysis with the proteomics data of the specific spore-release period based on LC-MS/MS approach. The Bt X022 genome consisted of one circular chromosomal DNA and seven plasmids, which were further functionally annotated using the RAST server. Comparative analysis of insecticidal substances showed that X022 contained genes coding for three Cry proteins (Cry1Ac, Cry1Ia and Cry2Ab) and a vegetative insecticidal protein (Vip3A). However, three insecticidal crystal proteins (ICPs) (Cry1Ca, Cry1Ac and Cry1Da) were detected by proteomics in the spore-release period. Moreover, a putative biosynthetic gene cluster and the metabolic pathway for poly-β-hydroxybutyrate in Bt X022 were deduced based on the comparative analysis of genomic and proteomic data, which revealed the metabolic regulation mechanism of carbon flux correlated with increased production of ICPs caused by Cu2+ . Hence, these results provided a deeper understanding of the genetic background and protein expression profile of Bt X022. This study established a foundation for directed genetic modification and further application of this new isolated Bt strain.